The Use of Bi-lobed Rotational Flap to Cover Large Body Defects: Two Clinical Cases - Špokevičius, Saulius (Lietuvos chirurgija, 2019)
The bi-lobed skin rotational flaps are commonly used mainly to cover facial tissue defects on the nasal tip and dorsal side, also on head areas, where skin and surrounding tissues are tight. Recent literature shows that the bi-lobed flap is used to cover defects in other body areas as well.This report shows two clinical cases where the bi-lobed flap was used to cover large skin and soft tissue defects after the excision of pathologically damaged skin and soft tissue lesions of the popliteal and the chest area. In both cases the recipient areas were adequately covered, and donor sites were closed primarily.
Keywords: bi-lobed flap; rotational flap; large soft tissue defects